Exploring Customer Knowledge from Social Media to Improve the Performance of Strategy - Tzu-Chun Weng (International School for Social and Business Studies, 2014)
Customer knowledge refers to the understanding of the customers' needs, wants, and aims. It is essential for an organization to align its processes, products, and services to build customer relationships. Managers need to understand how the acquisition and the use of customer-related knowledge create value for an organization. Customer knowledge management, which integrates knowledge management systems and customer relationship management systems, is a strategy that focuses on the task of gathering information, including finding effective ways to extract data from customers, as well as to locate and absorb information from other sources. Consequently, an organization can achieve the creation of new knowledge. This paper analyses the categories of customer knowledge, investigates the domains of customer knowledge, and explores customer knowledge management framework of social media. Then, information retrieval and information extraction of the social media are integrated to discover customer knowledge. Finally, customer knowledge management structure for workflow integration is proposed to align and integrate the strategy maps.